Characterization of the absorption of histidine and lead by Juglan regia L., Platanus L., and Pinus nigra L. using high-performance liquid chromatography-mass spectrometry and inductively coupled plasma-mass spectrometry - Ozen, Sukran Akkus; Yaman, Mehmet (Taylor & Francis Inc, 2016)
High-performance liquid chromatography-mass spectrometry and inductively coupled plasma - mass spectrometry were used for the determination of histidine and lead in Juglan regia L., Platanus L., and Pinus nigra L. leaves from industrial areas including Gaziantep City and Bursa City, Turkey. Distilled water was used for the extraction of histidine from plant material at 90 degrees C for 30min. The flow rate of the mobile phase, fragmentation potential, injection volume, and column temperature were optimized to be 0.2mL min(-1), 70V, 15 mu L, and 20 degrees C for the determination of histidine. The concentrations of histidine were from 7-9mg kg(-1) for Juglan regia L., 2-5mg kg(-1) for Platanus L., and 1-7mg kg(-1) for Pinus nigra L. The concentrations of Pb were from 1-42mg kg(-1) for Juglan regia L., 1-4mg kg(-1) for Platanus L., and 1-62mg kg(-1) for Pinus nigra L.
Keywords: High-performance liquid chromatography-mass spectrometry; histidine; hyperaccumulators; inductively coupled plasma-mass spectrometry; lead